PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR INFRASTRUKTUR DI DALAM BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Sundari, Rima; Ariska, Melita (LAND JOURNAL, 2025)
Typically, a company's stock price is expected to rise with good financial performance and fall with poor performance. However, this is not always the case in practice. For instance, PT Telkom reported a profit, but its stock price fell, whereas PT Jasa Marga experienced a rise in stock price along with a profit. This indicates that a company's stock price does not always align with its financial performance. Financial performance should be evaluated from the entirety of financial statements, including cash and receivables, not just profit or loss. Metrics like cash turnover and accounts receivable turnover can be used to assess these aspects. This report aims to examine the impact of cash turnover and accounts receivable turnover on stock prices in infrastructure sector companies listed on the IDX. The research employs quantitative methods and data analysis using IBM SPSS Statistics Version 27. The analytical techniques include normality tests, product moment correlation, multiple linear regression analysis, coefficient of determination, t-tests, and f-tests. The t-test results indicate that cash turnover does not have a significant impact on stock prices, while accounts receivable turnover positively and significantly affects stock prices. Keywords: Cash Turnover, Receivables Turnover, and Share Prices.